12Theatre and Performance. (31st May 2021) - Simpson, Hannah
Abstract: There is a sad irony in writing about theatre and performance scholarship at a time when most US and UK theatre are still closed as a result of the Covid-19 pandemic. However, for all its challenges, 2020 saw the publication of several noteworthy books that significantly advanced the field of theatre and performance studies, and which offer some cause for celebration. This review focuses on three major subject areas: 1. Performing Women, Women in Performance, 2. Tackling the Body, and 3. Social and National Borders. Several larger ideas unite the texts reviewed here, in varying constellations across these three sections: questions about representing identity, about failure and impossibility, and about unity, division, and the porous boundaries between the two. The term 'encounter' recurred with startling frequency across these eight texts, signalling a shared central concern with how far the performance space might offer a site of communion—or, at least, communication—in our fractious historical moment.